Significance of Lung Ultrasonography in the Follow-up and Treatment of Patients with Coronavirus Disease-2019 Having Respiratory Failure - Döndü Genç Moralar; Ülkü Aygen Türkmen; Ayşe Vahapoğlu; Hüseyin Gökçenoğlu; Ayfer Kaya Gök (Türk Yoğun Bakim Derneği Dergisi)

(untitled)
Objective:Lung involvement is commonly seen in patients with coronavirus disease-2019. In such cases, mechanical ventilation support and patient positioning are used to improve oxygenation. This study aimed to evaluate the effect of positioning performed under the guidance of ultrasound-guided patient positioning.Materials and Methods:Patients were divided into two groups: those who underwent lung ultrasonography and those who did not. Patients who underwent lung ultrasonography were positioned in a way that the region with larger infiltration area was upwards and then the groups were compared.Results:Arterial blood gas values of 103 patients were evaluated. An increased partial pressure of oxygen (PaO2) values at 2 and 12 hours after positioning was statistically significant in patients who were positioned under ultrasound guidance. In the group who did not undergo ultrasonography, an increased PaO/values was observed at 12 hours. When patients were evaluated according to their positions, an increased PaO2 values at 2 and 12 hours was statistically significant in the right lateral decubitus position. An increased PaO2 values was observed in prone position; however, it was not statistically significant.Conclusion:In our study, an increased oxygenation was observed in a short time, i.e., 2 hours, when patients were positioned under ultrasound guidance.